2010
DOI: 10.1088/0967-3334/31/9/010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency spectrum analysis of finger photoplethysmographic waveform variability during haemodialysis

Abstract: This study investigates the peripheral circulatory and autonomic response to volume withdrawal in haemodialysis based on spectral analysis of photoplethysmographic waveform variability (PPGV). Frequency spectrum analysis was performed on the baseline and pulse amplitude variabilities of the finger infrared photoplethysmographic (PPG) waveform and on heart rate variability extracted from the ECG signal collected from 18 kidney failure patients undergoing haemodialysis. Spectral powers were calculated from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 27 publications
2
38
1
Order By: Relevance
“…While previous studies have demonstrated clear links between PPGV and conditions associated with sympathetic changes [5,7,10,11,16,17,26], no study has ever been performed to establish a relationship between the spectral pattern of PPGV and a quantitative measure of vascular tone. In addition, since the suppression of sympathetic vascular tone could lead to a relative dominance of HF over LF power in PPGV [11,26], we also examined whether the PPGV spectral powers were useful for the categorical identification of patients in highly vasodilated states (indicated by the low SVR).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous studies have demonstrated clear links between PPGV and conditions associated with sympathetic changes [5,7,10,11,16,17,26], no study has ever been performed to establish a relationship between the spectral pattern of PPGV and a quantitative measure of vascular tone. In addition, since the suppression of sympathetic vascular tone could lead to a relative dominance of HF over LF power in PPGV [11,26], we also examined whether the PPGV spectral powers were useful for the categorical identification of patients in highly vasodilated states (indicated by the low SVR).…”
Section: Introductionmentioning
confidence: 99%
“…Infrared light can penetrate deep into the skin and subcutaneous tissue and is relatively insensitive to blood oxygenation [8,12], thus the resultant PPG signal reflects total blood volume change in the fingertip circulation, under the combined influences of central perfusion pressure and local sympathetic vascular control [2]. Similar to BPV, the frequency spectrum of PPG variability (PPGV) consists of both low frequency (LF) vasomotor waves, and high frequency (HF) respiratory fluctuations [5,10,11,16,17,23,26]. Sympathetic activation induced by active standing has been shown to augment normalized LF power of PPGV [5,17], whereas suppression of basal sympathetic tone by induction of anesthesia leads to a relative reduction in LF and enhancement of HF fluctuations [11,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that PPG signal contains information related to the cardiovascular dynamics. Some low frequency oscillations in PPG also reflect the function of autonomic nervous system [11,23,24]. The sources of these frequency components may be blood pressure control, thermoregulation, central baroreflex activity, vasomotoric rhythms, autonomous nervous system (ANS), neurogenic activity, myogenic rhythm, sympathetic modulation of peripheral vasculature (e.g., finger skin), and heart-synchronous pulse waveform [11,14,23,25,32].…”
Section: Introductionmentioning
confidence: 99%
“…Some low frequency oscillations in PPG also reflect the function of autonomic nervous system [11,23,24]. The sources of these frequency components may be blood pressure control, thermoregulation, central baroreflex activity, vasomotoric rhythms, autonomous nervous system (ANS), neurogenic activity, myogenic rhythm, sympathetic modulation of peripheral vasculature (e.g., finger skin), and heart-synchronous pulse waveform [11,14,23,25,32]. Other than the cardiac and respiratory rhythm, the sources of the low frequency oscillations present in PPG signal are not fully understood because of the highly complicated nature of the circulatory system, especially the interaction between the circulatory system and the ANS [15,24].…”
Section: Introductionmentioning
confidence: 99%